Visualising Safety, an Exploration Drawings, Pictures, Images, Videos and Movies - Le Coze, Jean-Christophe; Reiman, Teemu (SpringerBriefs in Applied Sciences and Technology; SpringerBriefs in Safety Management, 2023)
This open access book explores the role visual tools and graphical models play in safety management. It explains the importance of visualising safety, for teaching concepts, communicating ideas to peers, and raising awareness of potential threats through posters. Visualising Safety, an Exploration introduces graphical models which have been influential in promoting ideas of safety, and impacting the organisational design of safety mechanisms, including the Heinreich 'safety pyramid' and Reason's 'Swiss Cheese'. It analyses these models, as well as other forms of visualization, presenting viewpoints from academics and practitioners in the fields of safety science, history, ethnography and interface design. This brief will be of interest to anyone working in the field of safety management and design, including researchers, managers and students.